Setting the Table An Introduction to the Jurisprudence of Rabbi Yechiel Mikhel Epstein's Arukh HaShulhan - Broyde, Michael J. (Academic Studies Press, 2021)
One of the most basic questions for any legal system is that of methodology: how one interprets, analyzes, weighs and applies a mass of often competing legal rules, precedents, practices, customs, and traditions to reach final determinations and practical guidance about the correct legal-prescribed course of action in any given situation. Questions of legal methodology raise not only practical concerns, but theoretical and philosophical ones as well. We expect law to be more than the arbitrary result of a given decision maker's personal preferences, and so we demand that legal methodologies to be principled as well as practical. These issues are especially acute in religious legal systems, where the stakes are raised by concerns for respecting not just human, but divine law. Despite this, the major scholars and codifiers of halakhah, or Jewish law, have only rarely explicated their own methods for reaching principled legal decisions. This book explains the major jurisprudential factors driving the halakhic jurisprudence of Rabbi Yehiel Mikhel Epstein, twentieth century author of the Arukh Hashulchan-the most comprehensive, seminal, and original modern restatement of Jewish law since Maimonides. Reasoning inductively from a broad review of hundreds of rulings from the Orach Chaim section of the Arukh Hashulchan, the book teases out and explicates ten core principles of halakhic decision-making that animate Rabbi Epstein's halakhic decision-making. Along the way, it compares the Arukh Hashulchan methodology to that of the Mishna Berura. This book will help any reader understand important methodological issues in both Jewish and general jurisprudence.